Senescence and programmed cell death in plants: polyamine action mediated by transglutaminase - Del Duca, Stefano; Serafini-Fracassini, Donatella; Cai, Giampiero (Frontiers in Plant Science, 2014)
Research on polyamines in plants laps a long way of about 50 years and many roles have been discovered for these aliphatic cations. Polyamines regulate cell division, differentiation, organogenesis, reproduction, dormancy-break and senescence, homeostatic adjustments in response to external stimuli and stresses. Nevertheless, the molecular mechanisms of their multiple activities are still matter of research. Polyamines are present in free and bound forms and interact with several important cell molecules; some of these interactions may occur by covalent linkages catalyzed by transglutaminase, giving rise to ‘cationisation’ or cross-links among specific proteins. Senescence and PCD can be delayed by polyamines; in order to re-interpret some of these effects and to obtain new insights into their molecular mechanisms, their conjugation has been revised here. The transglutaminase-mediated interactions between proteins and polyamines are the main target of this review. After an introduction on the characteristics of this enzyme, on its catalysis and role in PCD in animals, the plant senescence and PCD models in which TGase has been studied, are presented: the corolla of naturally senescing or excised flowers, the leaves senescing, either excised or not, the pollen during self-incompatible pollination, the hypersensitive response and the tuber storage parenchyma during dormancy release. In all the models examined, transglutaminase appears to be involved by a similar molecular mechanism as described during apoptosis in animal cells, even though several substrates are different. Its effect is probably related to the type of PCD, but mostly to the substrate to be modified in order to achieve the specific PCD program. As a cross-linker of polyamines and proteins, transglutaminase is an important factor involved in multiple, sometimes controversial, roles of polyamines during senescence and PCD.